2001
DOI: 10.1021/je0003389
|View full text |Cite
|
Sign up to set email alerts
|

Liquid−Liquid Equilibria for Phenolic Compounds, Neutral Oils, and Nitrogen Bases at 313.15 K

Abstract: Liquid−liquid extraction with triethylene glycol as solvent, water as cosolvent, and hexane as countersolvent is being investigated as a process for the separation of phenolic compounds from neutral oils and nitrogen bases. To this end, liquid−liquid equilibria at 313.15 K and atmospheric pressure have been determined for the systems triethylene glycol + hexane + water + (phenol + aniline + benzonitrile + 5-ethyl-2-methyl pyridine + mesitylene) or (m-cresol + o-tolunitrile + o-toluidine + indene + pseudocumene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These runs were performed by loading the funnels with distilled water, with all other things being equal to the LLE experimental runs, and the two temperatures were found to be within ±0.1 K. During the LLE experiments, the funnels were shaken at regular intervals in order to accelerate equilibration and then left at rest to achieve phase separation, in line with the procedure reported by Venter and Nieuwoudt. 35,36 Some preliminary tests showed that 2 h was sufficient to achieve complete phase separation since clear phases were observed and stable solute concentrations in the two phases were measured. As a further confirmation, the LLE experimental results obtained for the widely studied binary system water + MIBK were found to be in good agreement with literature data, 37 as discussed in further detail in Section 3.1.…”
Section: Methodsmentioning
confidence: 99%
“…These runs were performed by loading the funnels with distilled water, with all other things being equal to the LLE experimental runs, and the two temperatures were found to be within ±0.1 K. During the LLE experiments, the funnels were shaken at regular intervals in order to accelerate equilibration and then left at rest to achieve phase separation, in line with the procedure reported by Venter and Nieuwoudt. 35,36 Some preliminary tests showed that 2 h was sufficient to achieve complete phase separation since clear phases were observed and stable solute concentrations in the two phases were measured. As a further confirmation, the LLE experimental results obtained for the widely studied binary system water + MIBK were found to be in good agreement with literature data, 37 as discussed in further detail in Section 3.1.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the removal of phenol and phenolic compounds from wastewater has taken on great environmental interest over the last years [4], [5]. Therefore, recovery of phenolic compounds from aqueous solution using liquid-liquid extraction method is industrially and economically important [6].…”
Section: Introductionmentioning
confidence: 99%